Possible Improvement to Matthews Tables in Areas of Canadian Data Holdings - Greenberg, D. A.; Sweers, H. E. (The International Hydrographic Review, 2015)
Depth corrections applied to the nominal depths for echo sounders, set to a mean soundspeed of 1463, are calculated using Canadian data holdings. Calculations are made by ten degree square and one degree square. Correlation between correction and surface temperature and between correction and season are examined. Comparisons are made with the present calculations and Matthews Tables.